2012
DOI: 10.1029/2011ja017402
|View full text |Cite
|
Sign up to set email alerts
|

Profile of strong magnetic field By component in magnetotail current sheets

Abstract: [1] The strong magnetic field B y component (in GSM coordinates) has been increasingly noticed to play an important role in the dynamics of tail current sheet (CS). The distribution profile of strong B y components in the tail CS (i.e., those with guide field), however, is not well known. In the present work, by using the simultaneous multipoint observations of Cluster satellites, the profile of a strong B y component in tail current sheets is explored, through detailed case studies, as well as in a statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 63 publications
(106 reference statements)
2
52
0
Order By: Relevance
“…Since, in tilted CSs, B y B z (Petrukovich et al, 2006), there is significant field-aligned current near the neutral plane (Shen et al, 2008). In this respect strongly titled CSs are similar to horizontal CSs with substantial B y component (Rong et al, 2012). In this paper we compare properties of strongly tilted and horizontal CSs and discuss the nature of the current in strongly tilted CSs.…”
Section: Y Vasko Et Al: Statistical Study Of Strongly Tilted Curmentioning
confidence: 99%
“…Since, in tilted CSs, B y B z (Petrukovich et al, 2006), there is significant field-aligned current near the neutral plane (Shen et al, 2008). In this respect strongly titled CSs are similar to horizontal CSs with substantial B y component (Rong et al, 2012). In this paper we compare properties of strongly tilted and horizontal CSs and discuss the nature of the current in strongly tilted CSs.…”
Section: Y Vasko Et Al: Statistical Study Of Strongly Tilted Curmentioning
confidence: 99%
“…Thus, all particles cross the neutral plane moving along trajectories, which can be described by the guiding-centre theory. This effect of asymmetry of the CS interaction with particles can play an important role in the Earth's magnetotail, where B y is provided by penetration of the interplanetary magnetic field (Cowley, 1981;Wing et al, 1995), by deformation of the neutral plane (Petrukovich, 2009) or by local currents (Artemyev, 2011;Rong et al, 2012). Particles usually come to the CS of the Earth's magnetotail from the sources in the Southern and Northern Hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…This requirement can be written as a kinetic equation df/dt = 0 for the distribution function of particles f , where d/dt is the total derivative (Pitaevskii and Lifshitz, 1981). Absence of particle collisions results in the conservation of the phase volume, and forbids directed drifts of particles in the invariant space (Sinitsyn et al, 2011), i.e.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Cluster data have shown the presence of CSs with a strong shear component (B y ∼ B 0 ) having uniform (Shen et al, 2008a;Rong et al, 2012) or bell-shape (Nakamura et al, 2008;Rong et al, 2012;Grigorenko et al, 2013) profiles. Due to the strong B y the current has a significant field-aligned component.…”
Section: Yvasko Et Al: Thin Current Sheets With Strong B Ymentioning
confidence: 99%
“…These CSs represent only a subclass of CSs with strong B y . The separate study is required for thicker CSs observed by Rong et al (2012) and Grigorenko et al (2013) in other periods of the Cluster mission.…”
Section: Yvasko Et Al: Thin Current Sheets With Strong B Ymentioning
confidence: 99%